2023
DOI: 10.1039/d2nj03671a
|View full text |Cite
|
Sign up to set email alerts
|

Bis-TTF-Ge derivatives: promising linear and nonlinear optical properties, a theoretical investigation

Abstract: In this work, based on bis(tetrathiafulvalenyldithio)-germane (bis-TTF-Ge), 37 compounds (noted T0-T36) are designed by introduction of donor and acceptor groups at different substituent positions. The ground state electronic structures, reactivity...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 97 publications
(151 reference statements)
0
15
0
Order By: Relevance
“…It should be noted that previous studies have indicated that the CAM‐B3LYP method, which was used in this work, is capable of producing an absorption spectrum that closely matches experimental results. Furthermore, this method has been shown to be effective in calculating both the static and dynamic non‐linear optical (NLO) responses [59–60] …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It should be noted that previous studies have indicated that the CAM‐B3LYP method, which was used in this work, is capable of producing an absorption spectrum that closely matches experimental results. Furthermore, this method has been shown to be effective in calculating both the static and dynamic non‐linear optical (NLO) responses [59–60] …”
Section: Resultsmentioning
confidence: 99%
“…The discovery of new NLO materials has emerged as one of the foremost challenges in research fields due to their immense potential for applications in diverse domains such as photonics, optoelectronics, optical communications, data storage, imaging, optical computing, and optical memory … etc. Quantum chemical calculation studies, conducted through various programs and methods, have demonstrated their utility in the design and discovery of nonlinear optical materials [25,59,78–82] …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These compounds have a wide range of applications in different fields, such as optical communication, optical computing, optical memory, and all-optical signal processing. 6–11 Photochromic compounds, such as stilbenes, azobenzenes, 12–14 diarylethenes, 15 spiropyrans, 16 and fulgides, 4,17 have excellent nonlinear optical responses (high hyperpolarizability). The combination between these two properties (photochromic and nonlinear optical) empowers generations of switchable second-order NLO materials.…”
Section: Introductionmentioning
confidence: 99%